Penentuan Lokasi Gudang Tiang ISP Menggunakan Metode COG dan AHP di PT XYZ Cirebon - Sari, Yunita; Fauzi, Muchammad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study is motivated by high transportation costs caused by direct material distribution from suppliers in Bandung to four project sites without passing through a central distribution warehouse. The distribution distances reach 152 km (C1), 154 km (C2), 139 km (C3), and 143 km (C4), resulting in increased logistics costs, difficulties in inventory control, and project completion delays. Consequently, the target of installing 100 utility poles per site within 20 days was not achieved, leading to a decline in project KPI performance. This study aims to determine the optimal distribution warehouse location using the Center of Gravity (COG) and Analytical Hierarchy Process (AHP) methods. The research adopts a descriptive approach with mixed methods. Data were obtained from company documents for cost information and from interviews and discussions to collect distance and distribution volume data, as well as to validate criteria and alternative locations. The COG analysis produced coordinates X = −6.702795806 and Y = 108.5351786; however, this point is located in an alley area and is therefore unsuitable as a warehouse site.